2020
DOI: 10.1259/dmfr.20190282
|View full text |Cite
|
Sign up to set email alerts
|

Examination of new parameters for sex determination of mandible using Japanese computer tomography data

Abstract: Objective: In the field of forensic science, sex discrimination of skeletons is an important identification item for personal identification. The individual sex discrimination method using skeletons includes a determination method using measurement values and a macroscopic form observation method. Both methods have advantage and disadvantage. In this study, we used the homologous model technique and principal component (PC) analysis to determine gender difference from morphology of the mandible. Methods and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Cross-sectional studies that have investigated the shape of the mandible often suffer from the same limitations 26,36,39 . There are several reports on the natural variation in morphology of the mandible, but these pertain to the adult mandible only [20][21][22][23][24][25] 33,34,40 , and have the most comparable data sets to the current study. Of the research with a similar age range as the present study, four studies employ PCA to investigate the morphology of the mandible 27,[33][34][35] .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Cross-sectional studies that have investigated the shape of the mandible often suffer from the same limitations 26,36,39 . There are several reports on the natural variation in morphology of the mandible, but these pertain to the adult mandible only [20][21][22][23][24][25] 33,34,40 , and have the most comparable data sets to the current study. Of the research with a similar age range as the present study, four studies employ PCA to investigate the morphology of the mandible 27,[33][34][35] .…”
Section: Discussionmentioning
confidence: 81%
“…Some studies investigated one aspect of the mandible, such as the condyle 10-13 , ramus 14 , mandibular canal [15][16][17][18] , or the lingula 16,19 . Several authors attempted to describe the shape [20][21][22][23][24][25] or the growth of the mandible as a whole [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] . Limitations of these studies mainly involve a small sample size, narrow age range, selection bias, or extensive manual input, such as landmark annotation.…”
mentioning
confidence: 99%
“…A new method that applies homologous models has been used in the 3D shape analysis of the human body. [12][13][14][15] The concept of homologous models is to represent the object shape by a polyhedron of homotopic geometric structure using the same number of anatomically mapped points; thus, it can be used to create an average shape using the arithmetic mean and compare the morphology of 3D objects. [12][13][14][15] For instance, Inoue et al 12 examined the left-right differences in mandibular ramus morphology using computed tomography (CT) data, whereas Suzuki et al 14 examined sex differences in the mandible.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic morphometry is a widely used research method for sex determination in humans (Suzuki et al, 2020; Uzuner et al, 2016) and domestic mammals (Gündemir et al, 2021) but has not yet been reported in poultry.…”
Section: Introductionmentioning
confidence: 99%